Factors influencing mental health help-seeking behavior among Bangladeshi youth (Dhaka University Journal of Biological Sciences, 2025)
The present study explored the factors that influence help seeking behavior among Bangladeshi youths within the framework of Health Belief Model (HBM). In pursuit of the objective, a cross-sectional design was employed followed by the quantitative method in data collection technique. A total of 220 college and university students, aged between 18 to 26 years (M = 21.5, SD = 2.1) were the study participants who completed the ‘The Bangla Translated Version of Health Belief Scale’ (Salleby, 2000), ‘The Bangla version of Sherer’s General Self - efficacy Scale’ (Ilyas 2005), ‘The Bangla Version of the Multidimensional Scale of Perceived Social Support’ (MSPSS) (Islam, 2021), including ‘A 20 items Mental Health Knowledge Checklist’ and ‘The five items Mental Health Help Seeking Intention Checklist’ developed by the researchers. To analyze data, Pearson product moment correlation and multiple regression analyses were conducted. Results showed significant positive moderate relationship between help seeking intention and General Health Motivation (r = 0.22, p < 0.05), Perceived Severity (r = 0.29, p < 0.001), Perceived Benefits (r = 0.31, p < 0.001), Perceived Barriers (r = 0.25, p < 0.001), and Mental Health Knowledge (r = 0.31, p < 0.001). Regression analyses claimed Perceived Severity (β = 0.16, p < 0.05), Perceived Benefits (β = 0.20, p < 0.05), Perceived Barriers (β = 0.16, p < 0.05), and Mental Health Knowledge (β = 0.21, p